Law Enforcement Policy on Violation of Illegal Cigarette Circulation in Indonesia (Study on Indonesian Customs Directorate General) - Maulana, Cahyo Baskoro Indra (Faculty of Law, Universitas Negeri Semarang, 2019)
The tax regulation is subject to a criminal act, then the Government in this Directorate of the General of Customs and Excise supervision, the circulation of illegal cigarettes. This research was conducted by the Directorate General of Customs and Excise as well as a crackdown on illegal cigarettes. This research uses the juridical normative method. Results of the study concludes as follows: first, the examination of the goods, examination of the goods, building or other place, letter or document to the goods, or against the people, against the Enforcement of goods and means of transport; and Locking, sealing, and / or sticking a necessary safeguards against goods or means of transport. Second, the efforts of the Directorate General of Performance and Surveillance, Dissemination, coaching against the cigarette companies, opening up information services and billing, complaints against criminal acts of illegal cigarettes.